The impact of an explicit grammar knowledge course on the development of grammatical awareness in UK native speakers' pre-service TESOL education - Rhian Webb (Literacy Trek, 2022)
This paper contributes to conversations which examine the effectiveness of grammar knowledge courses in native speaker (NS) UK pre-service TESOL education. A three-year longitudinal study was undertaken at a UK university. It explored 10 UK NS participants' ability to demonstrate grammatical awareness during their TESOL practicum after studying a 48-contact hour explicit grammar knowledge course before procedural TESOL education began. Quantitative and qualitative, deductive, and inductive thematic coding were undertaken using the participants' reflective teaching summaries and interview transcripts to identify examples of established grammar awareness themes. Findings indicated that the participants considered the process of gaining grammar knowledge challenging but essential for TESOL. Grammatical awareness was demonstrated through metalinguistic knowledge, metalanguage, noticing and language teaching beliefs during the practicum.